Flour Mill Workers Occupational Noise Exposure in Chandrapur City, Central India - Nimgade, Namrata R.; Kamble, R. K. (International Journal of Environment, 2018)
Assessment of occupational noise exposure of flour mill workers in Chandrapur city of central India was carried out during November 2015-January 2016. Total 62 flour mills were selected for this study comprising one, two and three grinding machines operating in the shop floor. The sound level meter was used to measure sound level at 50 cm and 3 meters from grinding machines at receiver’s position during operation. Noise monitoring was also recorded when one, two and three machines were operating individually and simultaneously. The results showed that noise levels when one grinding machine in operation in close proximity (50 cm) was in the range of 80-97 dB(A). Comparison of these observations with that of 3 meters distance; it was observed that noise levels got reduced and in the range of 70-77 dB(A). In the case of two machines in operation, it was in the range of 95-118 dB(A) at 50 cm distance and reduced to 75-95 dB(A) at 3 meters distance. This reduction in noise level was due to the propagation of noise in the ambient environment. Furthermore, daily noise exposure points, exposure points job per task and exposure points per hour were computed by using noise exposure calculator developed by Health and Safety Executive (HSE), United Kingdom. The computation from this calculator revealed that these attributes were directly depended upon noise levels in flour mills and duration of noise exposure. A positive linear Pearson’s correlation (p<0.01) was observed between noise level and exposure points per hour. Of the 65 flour mill workers surveyed, 70.76% reported a hearing problem, 23.07% headache at work and out of which 7.69% workers headache remains after completion of work also. Remedial measures to control noise exposure to flour mill workers such as ear plugs, ear muff, semi-insert are recommended.